2011
DOI: 10.1016/j.clinbiomech.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated ankle stretching on calf muscle–tendon and ankle biomechanical properties in stroke survivors

Abstract: Background-The objective of this study was to investigate changes in active and passive biomechanical properties of the calf muscle-tendon unit induced by controlled ankle stretching in stroke survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 50 publications
(54 reference statements)
6
85
1
4
Order By: Relevance
“…Previously, this mutant rat model has been used for neural studies exclusively (7,39,44). The mechanical properties of the spastic rat calf muscles found in the present study are consistent with the reduced functional range of motion and increased stiffness reported clinically in human limbs affected by spasticity (17,31,32,40), and the narrower active lengthforce curves estimated in in vivo studies on human GA (2,15,16). Thus the spastic rat model used in the present study mimics several important features of spasticity in human patients, and may be used to elucidate the mechanisms responsible for changes in muscle and limb mechanical properties observed in patients with spasticity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previously, this mutant rat model has been used for neural studies exclusively (7,39,44). The mechanical properties of the spastic rat calf muscles found in the present study are consistent with the reduced functional range of motion and increased stiffness reported clinically in human limbs affected by spasticity (17,31,32,40), and the narrower active lengthforce curves estimated in in vivo studies on human GA (2,15,16). Thus the spastic rat model used in the present study mimics several important features of spasticity in human patients, and may be used to elucidate the mechanisms responsible for changes in muscle and limb mechanical properties observed in patients with spasticity.…”
Section: Discussionsupporting
confidence: 89%
“…The absolute optimum length of GA was also lower because the absolute MTU length of GA at reference length was the same in the two groups (Table 1). These findings are consistent with length-force characteristics on the basis of net ankle joint moments and ultrasound imaging of spastic GA (2,15,16). The lower optimum length and narrower length-force curve can be explained by a number of factors: shorter muscle belly, fewer sarcomeres in series, stiffer and/or shorter tendon, or a decreased distribution of mean sarcomere length between fibers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The proper range of motion in dorsiflexion in the ankle joints, in particular, is essential for performing functional activities such as walking, running, climbing, and going down stairs normally [29]. After a stroke, the range of motion in the ankle joints is restricted by a decrease in the size of muscular fibers, a decline in the number of recruitment motor units, a failure to produce proper muscular strength owing to abnormal muscle tone, and weakness or contracture of the dorsi flexor [8], a restriction that poses the risk of declining balance ability [30].…”
Section: Discussionmentioning
confidence: 99%
“…Given et al [7] reported that the muscles around the ankle joints easily develop changes in their mechanical property because they have more type I muscle fibers and connective tissue than other muscles. Owing to the characteristics of the ankle joints, stroke patients are known to be more likely to have increased spasticity and shortened fascia of the gastrocnemius on the paretic side, producing a reduced range of motion in dorsiOriginal Article flexion in the ankle joints [8]. Such changes induce incorrect transmission of somatesthesia from the joint or the muscle receptors or motor response, accompanied by inappropriate ankle strategy, causing difficulty in balance control [9,10].…”
Section: Introductionmentioning
confidence: 99%